Google Daydream VR cookbook - Keene, Sam (Addison-Wesley : Pearson Education, 2019)
The Complete, Up-to-Date Guide to Building AR and VR Games Google's new ARCore and Daydream VR platforms enable you to deliver advanced augmented and virtual reality games and apps on a wide spectrum of modern Android devices. Now for the first time, there's a comprehensive deep dive into both ARCore and Daydream for every Android developer and designer. Multi-award-winning AR/VR developer Sam Keene takes a hands-on approach, leading you through all aspects of the ARCore and Daydream frameworks and SDKs, with step-by-step tutorials and advice for building pro-quality AR/VR games and apps. Keene presents his material as a cookbook of recipes to get you up and running with VR/AR development as fast and as painlessly as possible. The recipes in most chapters start by assembling the essential building blocks, which are pieced together to create something larger. You are then free to take these building blocks and turn them into your own creation. Keene also provides an extensive library of downloadable, up-to-the-minute ARCore and Daydream code to jumpstart your project. In addition, he takes you through crucial UX design principles and best practices learned from building large scale VR and AR apps at Google. Google Daydream VR Cookbook shows you how to: Install and explore the Google Daydream development tools Master basic and advanced Daydream Controller techniques Implement intuitive VR user interfaces Integrate audio, video, and realistic physics into your VR games Install and explore the ARCore SDK and development tools Learn how to build AR apps that solve real user needs Master AR game development using ARCore Optimize VR and AR game performance Whether you are a software developer, UX professional, visual designer, beginner, or you come from a different design field, this book is a great practical introduction to VR and AR.